2022
DOI: 10.3390/cancers14030563
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Stemness Features in 1059 Hepatocellular Carcinoma Patients from Five Cohorts: Prognosis, Treatment Response, and Identification of Potential Compounds

Abstract: Cancer stemness has been reported to drive hepatocellular carcinoma (HCC) tumorigenesis and treatment resistance. In this study, five HCC cohorts with 1059 patients were collected to calculate transcriptional stemness indexes (mRNAsi) by the one-class logistic regression machine learning algorithm. In the TCGA-LIHC cohort, we found mRNAsi was an independent prognostic factor, and 626 mRNAsi-related genes were identified by Spearman correlation analysis. The HCC stemness risk model (HSRM) was trained in the TCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 78 publications
(99 reference statements)
2
4
0
Order By: Relevance
“…A study by Mai et al proved that HCCs with higher mRNAsi scores had significantly worse overall survival based on an HCC matrix of more than 1000 HCC patients [52]. In this paper, we concluded the ICRPI was positively associated with mRNAsi, acting as a risk factor for the survival of HCC patients, which was consistent with Mai et al [53]. HRD had been used as a biomarker for therapy decision making [54].…”
Section: Discussionsupporting
confidence: 87%
“…A study by Mai et al proved that HCCs with higher mRNAsi scores had significantly worse overall survival based on an HCC matrix of more than 1000 HCC patients [52]. In this paper, we concluded the ICRPI was positively associated with mRNAsi, acting as a risk factor for the survival of HCC patients, which was consistent with Mai et al [53]. HRD had been used as a biomarker for therapy decision making [54].…”
Section: Discussionsupporting
confidence: 87%
“…The main characteristics of tumor stemness are the strong self-renewal ability and increased tumor heterogeneity [ 3 4 ]. Many studies have shown that tumor stemness plays an important role in tumor metastasis, differentiation, and drug resistance [ 9 , 10 ]. For example, USP22 was reported to promote the stemness of HCC cells by HIF1a pathways [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mai et al. developed an HCC stemness risk model as a potential indicator of TACE treatment response ( 17 ). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being small in number, CSCs are easily spread to distant organs, leading to HCC progression, recurrence ( 11 ) and metastasis ( 12 ). They are also implicated in therapy resistance, including sorafenib resistance ( 13 16 ), TACE refractoriness ( 17 ) and immunotherapy resistance ( 18 ). Moreover, CSCs could enhance immune evasion and induce an immunosuppressive microenvironment via the up-regulation of inhibitory molecules and the low expression of stimulatory molecules ( 19 ).…”
Section: Introductionmentioning
confidence: 99%